PENGUNGKAPAN PELAPORAN KEUANGAN MELALUI WEBSITE DAN FAKTOR-FAKTOR YANG MEMEGARUHI - Diatmika, I Gusti Putu Adi; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2017)
Developments in the field of information technology affect companies in running a business, one of them by utilizing the internet media. The rapid development of the internet creates a new way for companies to facilitate communication with investors. The use of the Internet as a medium of information disclosure will facilitate investors in obtaining company information. Investors can obtain the required information by looking at the information presented on the company's website pages. This study was conducted with the aim to determine the effect of firm size, profitability, leverage, auditor reputation, public ownership, and new share offerings to the disclosure of financial reporting through the website. The sample in this study used 81 non-financial companies listed on the Indonesia Stock Exchange in 2015. Determination of the number of samples using proportional stratified random sampling method, then grouped by type of industry. This study uses secondary data in the form of annual reports of companies listing on the Indonesia Stock Exchange until 2015 as well as observation of the company website. Methods of data analysis using multiple linear regression. The results show only company size, leverage and new share offerings that significantly influence the disclosure of financial reporting through the website. Variable profitability, auditor reputation and public ownership have no significant effect on financial report disclosure through website.